Exploring the Serverless First Strategy in Cloud Application Development - Cavalheiro, Adriano Prado; Schepke, Claudio (Anais Estendidos do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2023: Anais Estendidos do XXXV International Symposium on Computer Architecture and High Performance Computing, 2023)
This paper explores the Serverless First strategy in cloud application development. Serverless computing has gained popularity due to its flexibility and scalability. In our work, we provide a systematic review of the literature about the Serverless paradigm in cloud computing and an evaluation of the advantages of this approach by performing a comparative analysis among three ways for the implementation of an application: AWS Lambda, AWS Lambda with Chalice framework, and the traditional form using the Flask framework. The literature review results show the gains in scaling, cost reduction, and ease of maintenance achieved with the Serverless First strategy. However, some limitations and challenges were also highlighted, such as the greater complexity of the environment, less control over resources, resource limitations imposed by the cloud provider, and difficulties in debugging and managing the infrastructure. The case study demonstrates in practice that the Chalice framework provided the most straightforward and rapid implementation, the AWS Lambda without Chalice offered greater flexibility and control, and the Flask version allowed local testing and total control but required more manual setup and lacked automatic scalability.